THE LEVEL OF SEISMIC RESISTANCE OF RESIDENTIAL BUILDINGS IN ARCHITECTURE - Usarov Jamoliddin Tolkinovich (Academia Science Repository, 2023)
The article deals with the main problems of ensuring the seismic resistance of buildings with walls made of large blocks of sawn limestone, as well as the issues of moral and physical wear and tear of residential buildings, and extension of the service life. The possibility of applying the main methods for the reconstruction of block buildings with an increase in the number of stories, the prospects for implementation are considered. A technical and economic comparison of different options for increasing the number of stories is presented.